EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN PEMAHAMAN BAHAYA PENYALAHGUNAAN NARKOBA: Penyalahgunaan Narkoba, Layanan Bimbingan Kelompok - Tri Velyna (AL-ULUM | JURNAL PENDIDIKAN DAN PENGAJARAN, 2024)
Abstract: This research aims to reveal the effectiveness of group guidance services in increasing the understanding of class VIII students at BP Darush Sholah Middle School regarding the dangers of drug abuse. A research approach using a Quasi Experiment with a Pretest and Posttest Control Group Design was used to test whether group guidance services could increase students' understanding of the dangers of drug abuse. Two groups were selected using purposive sampling, namely students in class VIIIA and VIIIB at SMP BP Darush Sholah. Each group consists of 10 students. Group guidance services are applied to the experimental group, while group guidance services are not provided to the control group. Data on students' understanding of the dangers of drugs was collected using a Likert scale, then analyzed using the Wilcoxon Signed Ranks Test and Kolmogorov Smirnov Two Independent Samples with the help of SPSS version 20.00. The findings of this research are (1) there was a significant increase in students' understanding scores about the dangers of drugs after being given group guidance service treatment, (2) there was no increase in students' understanding scores about the dangers of drugs who were not given group guidance service treatment, (3) there were differences significant score of students' understanding of the dangers of drugs in the experimental group compared to the control group. Based on research findings, it can be concluded that students' understanding of the dangers of drugs can be improved through group guidance servic